Laman Web sebagai Media untuk Mempromosikan Filem Malaysia - Joshua, Ijau (Universiti Malaysia Sarawak, (UNIMAS), 2006)
Website has been a benchmark tor inflrrmution superhighways. Presently, websites are widely, used as one of the medium for marketing, commerce and has become the most populas media for communication. The advanced technology, in information and communication technology (ICT) has contributed to the development of wehsites. Currently. film industry has associated the web as part of promoting the updates on the latest film in the market. However, in Malaysia, the internet applicatio for film industry is still in a low level. This research investigates the problems that are found in the currrent Malaysian film database wehsites. Applicatiion on Malaysian identity is part of the main objective for the website implementation. This is based or the case studies that neglected the Malaysian identity as pant of promoting Malaysian film industry. At the end of the research, some recommendations on a more user friendly and interactive database website will be disscused.